J06 Pivot-HD: a phase 2, randomised, placebo-controlled study to evaluate the safety and efficacy of ptc518 in subjects with Huntington's disease. (12th September 2022) - Beers, Brian; Bredlau, Amy-Lee; Bhattacharyya, Anu; Kristensen, Allan; Golden, Lee; Klein, Matthew; Peltz, Stuart
Abstract : Background: Huntington's disease (HD) is caused by expansion of cytosine-adenine-guanine (CAG) trinucleotide repeats in the huntingtin (HTT) gene. The mutant protein is ubiquitously expressed and drives HD pathogenesis through a toxic gain-of-function mechanism. Animal models of HD demonstrate that reducing HTT protein levels alleviates HD symptoms. PTC518 is a splicing modifier that acts by promoting the inclusion of a pseudoexon containing a premature stop codon (psiExon), leading to HTT messenger RNA (mRNA) degradation and lowering of HTT levels. Results of a Phase 1 trial demonstrated PTC518's ability to lower HTT in healthy volunteers, supporting Phase 2 evaluation. Aims: The goal of the randomised, placebo-controlled, dose-ranging PIVOT-HD study (NCT05358717 ) is to evaluate safety and efficacy of PTC518 in subjects with HD. Methods/Techniques: 162 subjects ≥25 years, with genetically-confirmed HD (42–50 CAG repeats, inclusive), Unified HD Rating Scale (UHDRS)-independence scale score of 100, UHDRS total functional capacity score of 13, and a score of 0.18–4.93 inclusive on the normed HD prognostic index (PINHD) will be enrolled. Primary outcome measures: Number of participants with adverse events through Day 113 and change from baseline in blood total HTT at Day 85. Participants will be randomised 1:1 to part A (5 mg PTC518) or Part B (10 mg PTC518) and then randomised within each Part 2:1 to PTC518 or placebo. A Drug Safety Monitoring Board will undertake an unblinded review of safety data in Parts A and B and provide a recommendation on when Part C (20 mg PTC518) can be initiated.